Historical Biogeography and the Evolution of Hematophagy in Rhodniini (Heteroptera: Reduviidae: Triatominae) - de Paula, Alexandre Silva; Barreto, Carlos; Telmo, Mike Cerqueira Martins; Diotaiuti, Lileia; Galvão, Cleber (Frontiers in Ecology and Evolution, 2021)
The Rhodniini tribe is one of the five tribes in the subfamily Triatominae and is notorious for its domestic blood-sucking pests and vectors of Trypanosoma cruzi across Latin America. The human and economic costs of the Chagas disease in the American tropics are considerable, and these insects are of unquestionable importance to humans. We used mitochondrial rDNA (16S), nuclear ribosomal RNA (28S) and wingless (Wg) sequences to perform phylogenetic analysis to derive trees based on parsimony and maximum likelihood. Nucleotide sequences were used in molecular-clock analyses to estimate time divergence between species of Rhodniini. The potential distribution of each species was modeled and compared with Kappa statistic. Multivariate niches with bioclimatic variables were used to describe differences between the species using discriminant analysis. The results of this study indicate that the Rhodniini originated 17.91 Mya ago. Rhodnius domesticus is the oldest species having its origin at 9.13 Mya. Rhodniini are closely related to Salyavatinae that are specialist termite predators and diverged from this subfamily 30.43 Mya. Most species are clearly allopatric and have distinct bioclimatic niches. The colonization of bromeliads, palms trees and bird nests represent important events for the speciation of these taxa. The hematophagous habit can be described as a scenario where Rhodniini’s ancestor could be pre-adapted for the invasion of bromeliads, palm trees, and bird nests where they would find significant water availability and thermal damping. These environments are widely used by vertebrate inquilines that would be the source of food for the species of Rhodniini. Lastly, our results show an alternative position of Psammolestes in the phylogenetic tree.